2023
DOI: 10.3847/2041-8213/acac92
|View full text |Cite
|
Sign up to set email alerts
|

PHANGS–JWST First Results: Destruction of the PAH Molecules in H ii Regions Probed by JWST and MUSE

Abstract: Polycyclic aromatic hydrocarbons (PAHs) play a critical role in the reprocessing of stellar radiation and balancing the heating and cooling processes in the interstellar medium but appear to be destroyed in H ii regions. However, the mechanisms driving their destruction are still not completely understood. Using PHANGS–JWST and PHANGS–MUSE observations, we investigate how the PAH fraction changes in about 1500 H ii regions across four nearby star-forming galaxies (NGC 628, NGC 1365, NGC 7496, and IC 5332). We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 88 publications
5
30
0
Order By: Relevance
“…Continuum-subtracted 3.3 μm PAH maps (F335M PAH ) are constructed using the method outlined in Sandstrom et al (2023) that leverages the F300M and F360M imaging to infer the underlying continua. No continuum subtraction is carried out for the F770W or F1130W imaging since the stellar contributions at these wavelengths are minor and the dust emission appearing in these two bands is dominated by PAH features (Smith et al 2007;Egorov et al 2023;Hassani et al 2023). Future work will explore the impact of using, for example, the F1000W imaging as a proxy for the wavelength-adjacent continuum for the F770W and F1130W bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuum-subtracted 3.3 μm PAH maps (F335M PAH ) are constructed using the method outlined in Sandstrom et al (2023) that leverages the F300M and F360M imaging to infer the underlying continua. No continuum subtraction is carried out for the F770W or F1130W imaging since the stellar contributions at these wavelengths are minor and the dust emission appearing in these two bands is dominated by PAH features (Smith et al 2007;Egorov et al 2023;Hassani et al 2023). Future work will explore the impact of using, for example, the F1000W imaging as a proxy for the wavelength-adjacent continuum for the F770W and F1130W bands.…”
Section: Discussionmentioning
confidence: 99%
“…Our evidence for higher levels of PAH ionization is conceptually consistent with the work of other PHANGS-JWST efforts appearing in this Issue. Egorov et al (2023) analyze the F1130W/F770W parameter, widely considered to be a tracer of the ratio of neutral to ionized PAHs (Draine & Li 2001;Maragkoudakis et al 2020), in H II regions in NGC 628, NGC 1365, NGC 7496, and IC 5332 and find lower values of F1130W/F770W in regions with higher [S III]/[S II] ratios, indicating harder radiation fields. Chastenet et al (2023) probe PAH band ratios across the disks of the four galaxies and find evidence of hotter, highly ionized PAHs in the vicinity of H II regions that are defined by the radiation from young stars.…”
Section: Notesmentioning
confidence: 99%
“…These targets have deep, high-resolution, ancillary information from the Atacama Large Millimeter/submillimeter Array (Leroy et al 2021), Very Large Telescope-MUSE (Emsellem et al 2022), Hubble (Lee et al 2022), AstroSat (H. Hassani et al 2023, in preparation), and more. Combining NIRCam imaging of the 3.3 μm PAH feature with MIRI imaging of the 7.7 and 11.3 μm features enables one of the first studies of the variation of both PAH size and charge over large regions of nearby galaxies (Chastenet et al 2023), in HII regions (Egorov et al 2023), and near young star clusters and associations (Dale et al 2023;Rodriguez et al 2023). As part of this effort, we found it was necessary to adjust the current best NIRCam medium-band continuum removal prescription in the literature from Lai et al (2020) to account for PAHemission (or related dust-emission) contamination of F360M filter (Section 3).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we find systematically elevated line widths in the interior of both bubbles relative to their shells, and even measure FWHM values of more than 100 km s −1 in the Phantom Void (though at these very low signal-to-noise ratios < 10 note there is a bias toward overestimating line widths). Such high values of the line width could be indicative of SN feedback contributing to increased turbulence within the center of the bubble (Egorov et al 2023). Near the shell, we directly identify SN remnants via their broadened [S II]6716 line emission and increased [O I]/Hα line ratios (Figure 5; J.…”
Section: Ionized Gasmentioning
confidence: 89%
“…Specifically, the wavelength coverage of the Mid-Infrared Instrument (MIRI) is perfectly suited to this task, as it is sensitive to several polycyclic aromatic hydrocarbon (PAH) emission features (e.g., at 7.7 μm; see Draine & Li 2007;Smith et al 2007;Li 2020). Emission from PAHs is particularly useful in tracing the shells of feedback-driven bubbles (e.g., Pineda et al 2022), due to (a) the increased gas densities found in swept-up shells (PAHs are generally well mixed with the gas and illuminated by the average interstellar radiation field such that they trace the gas column very sensitively; e.g., Regan et al 2006;Leroy et al 2013;Chown et al 2021;Gao et al 2022;Leroy et al 2023), (b) the high number of ionizing photons emitted by the OB association powering the bubbles, leading to PAHs being destroyed in the photoionized interiors of the bubbles (e.g., Galliano et al 2018;Chastenet et al 2023aChastenet et al , 2023bEgorov et al 2023), and (c) the low optical depth from the shell interior to the edge, which will allow far-UV photons to easily heat the small dust grains (e.g., Draine & Li 2007;Draine 2011;Hensley & Draine 2021). Together, these cause the edges of bubbles to appear with high contrast against their interior PAH emission (e.g., Churchwell et al 2006;Watson et al 2008).…”
Section: Introductionmentioning
confidence: 99%